PEMANFAATAN TANAMAN TOGA DALAM UPAYA MENINGKATKAN KESEHATAN KELUARGA DAN MASYARAKAT DI NAGARI TIGO SUNGAI INDERAPURA - Angela, Lia; Putri, Wanda Melyana; Saputri, Utari Aulia Tianda; Ramadani, Ramadani (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Nagari Tigo Sungai Inderapura is one of the nagari located in West Sumatra Province. To continue to maintain this good reputation, real efforts need to be made by involving all elements of society in preserving the diversity of family medicinal plants produced, through the use of family medicinal plants. The specific objectives of this PKM activity include increasing the efficiency and effectiveness of family medicinal plants in the daily life of the Nagari Tigo Usngai Inderapura Community. The main target to be achieved based on the available objectives is that the Tigo Sungai Inderapura community is able to implement and cultivate family medicinal plants in community life. Meanwhile, the specific target of this activity is that the community is able to improve the quality of family medicinal plants that are used and cultivated